Cancer Survival Trends in Southeastern China, 2011–2021: A Population-Based Study - Zhou Y; Wen Y; Xiang Z; Ma J; Lin Y; Huang Y; Chen C (Clinical Epidemiology, 2024)
Yan Zhou,1,* Yeying Wen,1,* Zhisheng Xiang,1,* Jingyu Ma,1 Yongtian Lin,1 Yongying Huang,1 Chuanben Chen2 1Department of Epidemiology, Clinical Oncology School of Fujian Medical University and Fujian Cancer Hospital, Fuzhou, People’s Republic of China; 2Department of Radiation Oncology, Clinical Oncology School of Fujian Medical University and Fujian Cancer Hospital, Fuzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuanben Chen, Department of Radiation Oncology, Clinical Oncology School of Fujian Medical University and Fujian Cancer Hospital, Fuzhou, People’s Republic of China, Tel +86-591-83660063, Email chenchuanben2010@126.comPurpose: The 5-year cancer survival rate among Chinese patients is lower than that among patients in developed countries and varies widely across geographic regions. The aim of this study was to analyse the 5-year relative cancer survival rate in southeastern China, between 2011 and 2021.Patients and Methods: We utilised population-based statistics from 12 cancer registries in Fujian, China. Study population data were up to date as of Dec 31, 2019, and survival outcome status was updated as of Dec 31, 2021. We used the ICD-10 and the ICD-O-3 to categorize all cancer cases. We analysed the 5-year relative survival for cancers combined and different cancer types stratified by sex, urban and rural areas, and age. Survival estimates were stratified according to calendar period (2011– 13, 2014– 15, 2016– 18 and 2019– 21).Results: Ultimately, a total of 160,294 cancer patients were enrolled in the study. In 2011– 13, 2014– 15, 2016– 18 and 2019– 21, the age-standardised 5-year relative survival for cancers combined were 29.1% (95% CI: 28.6– 29.7), 31.5% (95% CI: 31.0– 32.0), 36.8% (95% CI: 36.4– 37.3) and 39.1% (95% CI: 38.7– 39.6), respectively. The age-standardised 5-year relative survival for lung, prostate, larynx, colon-rectum, kidney and bone cancers increased 4.3%, 4.0%, 3.8%, 3.4%, 3.4% and 2.70%, respectively. Cancers with high 5-year relative survival rates (> 60%) in 2019– 21 included thyroid, testis, breast, bladder, cervix, prostate and uterus cancers. The 5-year survival rates in 2019– 2021 was higher for females than for males (47.8% vs 32.0%) and higher in urban areas than in rural areas (41.7% vs 37.1%). Relative survival rates decreased with increasing age.Conclusion: The 5-year cancer survival in Fujian Province increased between 2011 and 2021 but remained at a low level. Building a strong primary public health system may be a key step in reducing the cancer burden in Fujian Province.Keywords: relative survival, cancer, population-based study, cancer registry